Paciente masculino de 35 años de edad con diagnóstico de neumonía intrahospitalaria. - Deker Narváez, Denisse Alexandra (2021)
The present clinical study is based on a 35-year-old male patient who attended the hospital with his spouse due to a complication in his underlying disease. He presented 4 days after his admission relevant symptoms such as a productive evolution cough and fever. The objective of this study is based on establishing adequate treatment for the diagnosis of INTRAHOSPITAL PNEUMONIA that the patient presents. After due follow-up and treatment implemented in this clinical study after obtaining information on the etiological agent causing the disease and at the same time its origin in this in-hospital case, a favorable outcome was obtained in the patient, with oxygen therapy being the main procedure indicated in the patient accompanied by a treatment with aerosol therapy, and at the same time a proper administration of antibiotic therapy